A black electrodeposited copper–tin (Cu–Sn) alloy film for solar thermal absorbers. (2nd January 2018) - Katırcı, R.
ABSTRACT: This study was aimed at identifying the organic molecules oxidising the Cu–Sn alloy coating in a sulphate electroplating bath to form a black solar absorbing surface. For this purpose, 20 organic chemicals were used separately in the electroplating bath to obtain Cu–Sn alloy thin films. The films were characterised using the spectroscopic methods. It was found that addition of EDTP ( N, N -dimethyl-dithiocarbamylpropyl sulphonic acid, sodium salt) provided the best optical parameters.